Biotechnology and Biodefense Enterprise: An Industry Perspective on Defence Acquisition. Issue 1 (31st December 2022) - Yeh, Kenneth B.; Du, Eric; Olinger, Gene; Boston, Donna
ABSTRACT: Biotechnology is gaining priority along with other rapidly evolving disciplines in science and engineering due to its potential for innovating the modern military. The broad nature of biotechnology is directly relevant to the military and defence sector where the applications span clinical diagnostics, medical countermeasures and therapeutics, to environmental remediation and biofuels for energy. Although the process for a commercial biotech research and development (R&D) pipeline and the Department of Defence (DOD) acquisition cycle both aim to result in products, they follow two distinctly different pathways. In the biotech industry, the pipeline progresses from basic to applied science that includes design and R&D, commercialisation and product launch, where market forces and financial returns on investment drive priorities. Along the way, the scientific and iterative nature of R&D often results in several candidates for a given assay, drug, therapeutic or vaccine, many of which are unsuccessful or wind up in the so-called valley of death. The DOD acquisition process is a multi-phase and often multi-decade cradle-to-grave product lifecycle engrained in mission requirements, warfighter needs and creating legacy programmes of record. The biotech industry is composed of many small R&D and 'big pharma' companies that meet DOD's unique medical mission requirements. These small R&D companies considered that non-traditional DOD acquisition partners are developing new innovations in biotechnology, but the complex DOD acquisition process is challenging for these small start-ups to navigate. Technology solutions that gain support through DOD acquisitions are able to successfully develop their products and bridge the valley of death by obtaining much needed funding for advanced development, test and evaluation, and demonstration through clinical trials. Our analysis profiles three case histories involving private-public partnerships that yielded biotech products developed through the DOD acquisition cycle that continues to meet current and future medical mission requirements.